2023
DOI: 10.1021/acs.jpcc.3c06393
|View full text |Cite
|
Sign up to set email alerts
|

Strain-Dependent Optical Properties of Monolayer WSe2

Yanhui Lv,
Mohamed Abid,
H. H. Cheng
et al.

Abstract: Monolayer WSe 2 exhibits a fascinating optical dark exciton ground state, which holds significant promise for advancing single-photon source and quantum information processing. In this study, we systematically explored the temperature-and straindependent optical properties of monolayer WSe 2 using a threedimensional silicon-based nanowrinkle structure as a template. We observed emission from a variety of excitonic states, including bright exciton (X 0 ), bright trion (X T ), dark exciton (X D ), and dark trion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…On the other hand, enhancement of the valley polarization of WSe 2 monolayer excitons has been pursued using techniques such as optical pumping, magnetic fields, electrical fields, , strain, defects, , and the formation of heterojunctions . Recent advances have demonstrated that site-controlled quantum emission from specific excitons, particularly enhanced emission from dark excitons, can be achieved using templates with prepatterned nanostructures . Furthermore, the valley polarization of bright excitons can be influenced by an yttrium iron garnet (YIG) substrate through the magnetic proximity effect. Therefore, it is appealing to pose the following questions: Is it possible to simultaneously attain robust emission and elevated valley polarization of dark excitons using a prepatterned nanostructured YIG template?…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, enhancement of the valley polarization of WSe 2 monolayer excitons has been pursued using techniques such as optical pumping, magnetic fields, electrical fields, , strain, defects, , and the formation of heterojunctions . Recent advances have demonstrated that site-controlled quantum emission from specific excitons, particularly enhanced emission from dark excitons, can be achieved using templates with prepatterned nanostructures . Furthermore, the valley polarization of bright excitons can be influenced by an yttrium iron garnet (YIG) substrate through the magnetic proximity effect. Therefore, it is appealing to pose the following questions: Is it possible to simultaneously attain robust emission and elevated valley polarization of dark excitons using a prepatterned nanostructured YIG template?…”
Section: Introductionmentioning
confidence: 99%